Typology of Green Consumers in Mexico: A Psychographic Profile of Green Consumer - Daniel Bucio Gutiérrez; José Ignacio Azuela Flores; Karla Paola Jiménez Almaguer (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales)
The purpose of this paper is to identify the profile of green consumers in Mexico based on the Inten-tion of Green Purchase and the Attitude Towards Green Consumption. In order to achieve this, in addition to the Exploratory and Confirmatory Fac-tor Analysis necessary to construct the latent varia-bles, the Hierarchical and Non-Hierarchic Cluster analyzes (k-means) required to define the segments were estimated. The data was obtained from the Green Consumption Survey applied to final consu-mers. The results show two typologies of the green consumer: the skeptics, who are characterized by their lack of information and selfish attitude to-wards the environment, and the altruists who stand out for their extensive information and concern for the environment.